FAKTOR PENYEBAB FLUKTUASI EKSPOR TIMAH BANGKA BELITUNG KE SINGAPURA TAHUN 2017-2019 - Riza Rahmawati; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The export and import activities have always been performed widely in order to maintain the cooperation and the connection among the bilateral countries. Indonesia as the country which has lots of natural resources is able to perform export activity which includes raw material to the countries which have no or limited material in producing it in the country. One of the Natural assets of Indonesia is Timah because Indonesia is located in the area of the Southeast Asia tin belt which make the country has 40% of Timah of all over the world in total.. This research was composed by using liberalism perspective with the theory of export which has the country and nation analytical level, the data of the research was obtained by using the qualitative-descriptive method and a literature review was also been done in obtaining the data. The data which used is the secondary data which obtained from the Statistical Centre (BPS), Timah official websites, and the ministry websites which provide the information of the export and the phenomena of fluctuation which appeared in 2017-2019. The result of the research shows the existence of the factor which causes the fluctuation of the export of Timah of Bangka Belitung to Singapore in 2017 to 2019 is the application of price instruction and the regulation which established in performing the export of Timah abroad with its own requirements which is not easy to do becoming one of the factors of the fluctuation in the export of Timah in 2017 to 2019. The increase that occurred in 2017 was at 4456 Mton, while the decrease that occurred in 2018 was 3488 Mton, then it increased in 2019 with an export value of 5328 Mton. It is not only about the price labelled and the requirements of the export activities which regulated by the government of Indonesia which categorized as the factor of the fluctuation but also the extern factors which are the Metal Exchange, the universal economic growth and the exchange of Dollar are also categorized as the factor of the fluctuation of the export of Timah of Bangka Belitung to Singapore. Keyword: Lead Export , Fluctuation Factor, Liberalism perspective